PENGARUH GAYA HIDUP DAN KEPERCAYAAN TERHADAP MINAT PEMBELIAN ULANG PADA PELANGGAN GOFOOD DI KOTA MALANG - Maulidah, Salisa; Budiarti, Lina; Sulasari, Ayu (Jurnal Aplikasi Bisnis, 2024)
The advancement of information technology in the 4.0 era has a major impact on people’s lifestyles. Repurchase interest is influenced by a number of important elements, including trust and lifestyle. Repurchase interest in GoFood declined from the top choice in 2021 to the second choice in 2022. The purpose of this study is to test how lifestyle and beliefs affect the desire of GoFood Malang City consumers to make their next purchase. Repurchase interest is a dependent variable, while lifestyle and belief variables are independent variables in this quantitative study. Purposive sampling was used to select 100 GoFood customers in Malang City to receive a questionnaire containing data. Hypothesis testing and multiple linear regression are used in the data analysis process. The results showed that lifestyle and trust had a positive and significant effect on repurchase interest, both partially and simultaneously. It is recommended that GoFood consider the diverse lifestyles of customers and improve service quality to build trust, thereby increasing repurchase intention.